2020
DOI: 10.1016/j.avsg.2020.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Wound Care during COVID-19 Pandemic

Abstract: The spread of the COVID-19 has profoundly affected the way we conduct our medical practices, resulting in a decrease in necessary medical care, including the wound healing specialty. The actual period of COVID-19 pandemic limits the ability to practice wound healing in normal conditions. Patients with vascular leg ulcers represent an extremely vulnerable population, with poor quality of life caused by the pain directly related to both ulcer duration and ulcer area. 1 These patients must not be overlooked becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 2 publications
0
24
0
4
Order By: Relevance
“…57 A small and interesting study by a team from Italy indicated that the COVID-19 pandemic had a significant impact on management of wound dressings and compliance with appointments as it related to VU. 58 As a result, providers tried alternate methods such as simplifying the dressing method and a small group even opted to make videos to help patients do their own dressings. From the patient's perspective, there was a decrease of appointment frequency in 59% of the cases and nearly 61% of VU patients did not maintain any contact with their provider, and some (13%) did not change their dressing at all during the pandemic.…”
Section: Venous Ulcersmentioning
confidence: 99%
“…57 A small and interesting study by a team from Italy indicated that the COVID-19 pandemic had a significant impact on management of wound dressings and compliance with appointments as it related to VU. 58 As a result, providers tried alternate methods such as simplifying the dressing method and a small group even opted to make videos to help patients do their own dressings. From the patient's perspective, there was a decrease of appointment frequency in 59% of the cases and nearly 61% of VU patients did not maintain any contact with their provider, and some (13%) did not change their dressing at all during the pandemic.…”
Section: Venous Ulcersmentioning
confidence: 99%
“…Finally, over 15% stated that their wound had worsened. 6 Our findings show that the COVID-19 pandemic had a considerable impact on wound care in Germany as well, but to a lesser extent. Obvious reasons may be the higher incidence of COVID-19 cases and, subsequently, the higher exposure risk in Italy.…”
Section: Discussionmentioning
confidence: 57%
“…Recent studies discussed the collateral damage of overburdened health care systems and restricted access to non-essential health services during the COVID-19 pandemic with regard to patients with chronic leg ulcers. 6,11,12 For example, an Italian survey asked medical doctors, nurses, caregivers, and 28 patients with chronic leg ulcers about their perception of the impact of COVID-19 on wound care. This study showed that over 75% of the patients discontinued their consultations at the wound clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This complication highlights that the sudden outbreak of COVID-19 makes the management of wounds even more complicated than usual, for both the patients and their caregivers. ( 10 , 11 )…”
Section: Discussionmentioning
confidence: 99%